2013
DOI: 10.1371/journal.pone.0071972
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Drug-Resistance Surveillance among Treatment-Experienced and -Naïve Patients after the Implementation of Antiretroviral Therapy in Ghana

Abstract: BackgroundLimited HIV-1 drug-resistance surveillance has been carried out in Ghana since the implementation of antiretroviral therapy (ART). This study sought to provide data on the profile of HIV-1 drug resistance in ART-experienced and newly diagnosed individuals in Ghana.MethodsSamples were collected from 101 HIV-1-infected patients (32 ART-experienced cases with virological failure and 69 newly diagnosed ART-naïve cases, including 11 children), in Koforidua, Eastern region of Ghana, from February 2009 to J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
22
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 16 publications
(22 reference statements)
9
22
1
Order By: Relevance
“…Although another study in the Eastern regional capital, Koforidua, in 2009, found no major resistance mutations in that ART-naïve group, 18 the results from this study and that of the first-ever threshold survey carried out in Ghana in two different sites in the Eastern Region 10 show an increasing trend. This calls for surveillance for tHIVDR in a larger study population in the eastern region and elsewhere in Ghana to further understand the extent of its spread and introduce appropriate measures to curb its devastating effects on the nation's antiretroviral therapy programme.…”
contrasting
confidence: 66%
“…Although another study in the Eastern regional capital, Koforidua, in 2009, found no major resistance mutations in that ART-naïve group, 18 the results from this study and that of the first-ever threshold survey carried out in Ghana in two different sites in the Eastern Region 10 show an increasing trend. This calls for surveillance for tHIVDR in a larger study population in the eastern region and elsewhere in Ghana to further understand the extent of its spread and introduce appropriate measures to curb its devastating effects on the nation's antiretroviral therapy programme.…”
contrasting
confidence: 66%
“…This shows that more HIV infected individuals are being recruited unto HAART. This results are in agreement with the findings of Atuyambe et al [17] and Nii-Trebi et al [15] who also recorded The mean duration of HAART is denoted by the mean difference between Post HAART age and pre-HAART age. The participants have been on HAART for a long duration as the post-HAART age is significantly higher than the pre-HAART age.…”
Section: Discussionsupporting
confidence: 93%
“…Better rates of HIV replication suppression is achieved in patients administered with efavirenz-based HAART who received tenofovir-emtricitabine compared with patients who received zidovudine-lamivudine [14]. In order to avoid the toxicities associated with Zidovudine use, especially in individuals with anaemia, global access to tenofovir has been increased [15]. Not many studies on the haematological parameters abnormalities in HIV infected persons have been conducted in sub Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
“…It would seem, therefore, that the development of resistant quasi-species is inevitable in the event of suboptimal compliance with ART (Condra et al, 1995;Nii-Trebi et al, 2013;Richman et al, 1994). Paterson et al found that the incidence of virologic failure increased with decreasing adherence: 22% of patients had documented virologic failure with 95% or greater adherence whereas failure rates increased to 61% with less than 94.9% adherence (Ickovics et al, 2002;Paterson et al, 2000).…”
Section: Requirement For Lifelong Adherence and Pill Burdenmentioning
confidence: 99%